2018
DOI: 10.1200/jco.2018.36.18_suppl.lba4001
|View full text |Cite
|
Sign up to set email alerts
|

Unicancer GI PRODIGE 24/CCTG PA.6 trial: A multicenter international randomized phase III trial of adjuvant mFOLFIRINOX versus gemcitabine (gem) in patients with resected pancreatic ductal adenocarcinomas.

Abstract: LBA4001 Background: FOLFIRINOX is more effective than gem as first-line treatment in metastatic pancreatic cancer for patients (pts) with good performance status. This trial assessed the benefit of mFOLFIRINOX in the adjuvant setting. Methods: PRODIGE 24/CCTG PA.6 is a phase III multicenter, randomized clinical trial. Pts aged 18-79 years with histologically proven pancreatic ductal adenocarcinomas, 21-84 days after R0 or R1 resection, WHO PS ≤1, adequate hematologic and renal function, and no cardiac ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 0 publications
1
80
0
Order By: Relevance
“…However, other guidelines recommend an initial surgical approach, to be followed by chemotherapy . Seemingly supportive of this latter strategy, data from the recently presented Gastrointestinal PRODIGE 24/Canadian Cancer Trials Group PA.6 study revealed that the survival of patients who received adjuvant folinic acid (leucovorin), 5‐fluorouracil, irinotecan, and oxaliplatin (FOLFIRINOX) after pancreatectomy was 54.4 months, which was longer than that reported in any previously published therapeutic trial for any stage of pancreatic cancer . However, we cannot overemphasize the degree to which the patients enrolled in that trial were super‐selected: all were required to have a postoperative carbohydrate antigen19‐9 level less than 180 U/dL, an Eastern Cooperative Oncology Group performance status of 0 or 1, and no major comorbidity; and all needed to be physiologically suitable to receive FOLFIRINOX within 12 weeks of pancreatectomy.…”
Section: Comparison Of Possible Trial Designs For Patients With Brpcsupporting
confidence: 65%
“…However, other guidelines recommend an initial surgical approach, to be followed by chemotherapy . Seemingly supportive of this latter strategy, data from the recently presented Gastrointestinal PRODIGE 24/Canadian Cancer Trials Group PA.6 study revealed that the survival of patients who received adjuvant folinic acid (leucovorin), 5‐fluorouracil, irinotecan, and oxaliplatin (FOLFIRINOX) after pancreatectomy was 54.4 months, which was longer than that reported in any previously published therapeutic trial for any stage of pancreatic cancer . However, we cannot overemphasize the degree to which the patients enrolled in that trial were super‐selected: all were required to have a postoperative carbohydrate antigen19‐9 level less than 180 U/dL, an Eastern Cooperative Oncology Group performance status of 0 or 1, and no major comorbidity; and all needed to be physiologically suitable to receive FOLFIRINOX within 12 weeks of pancreatectomy.…”
Section: Comparison Of Possible Trial Designs For Patients With Brpcsupporting
confidence: 65%
“…A recent study reported at ASCO this year, which was not included in this meta‐analysis as was not within timeframe studied, describing the results of a phase III randomized clinical trial investigating adjuvant modified 5‐fluorouracil/irinotecan/oxaliplatin (FOLFIRINOX) versus gemcitabine in 493 patients with resected PDAC, reported an improvement in median DFS for the modified FOLFIRINOX arm (21.6 vs 12.8 months respectively). Node positive disease (HR, 1.67; 95% CI, 1.25‐2.22; P < 0.001) and R1 resection status (HR, 1.45; 95% CI, 1.16‐1.81; P = 0.001), were identified as poor prognostic markers for DFS …”
Section: Discussionmentioning
confidence: 99%
“…FOLFIRINOX (fluorouracil, folinic acid, irinotecan and oxaliplatin) improves disease-free survival when compared with gemcitabine alone (21.6 months versus 12.8 months) but is associated with increased toxicity. 26,27 Gemcitabine plus oral capecitabine is superior to gemcitabine alone (overall survival of 28.0 months versus 25.5 months). 28 The use of neoadjuvant chemotherapy for resectable disease is of uncertain benefit, although there is a trend towards increased use.…”
Section: Chemotherapymentioning
confidence: 99%